Meteorological-hydrodynamic model coupling for safe inland navigation of waterway stretches in dam reservoirs, using a scarce database - Mattosinho, Germano de Oliveira; Maciel, Geraldo de Freitas [UNESP]; Ferreira, Fabiana de Oliveira; Vieira, Adriana Silveira; Sáo, Yuri Taglieri [UNESP] (FapUNIFESP (SciELO), 2022)
The SWAN (Simulating WAves Nearshore) numerical model has been used and validated in numerous studies of open coastal and estuarine regions. Its application on inland or restricted waters (dam reservoir) is not only innovative and challenging, but also an important scientific contribution, filling a gap in the literature. We analyze the performance of the SWAN in the characterization of the agitation caused by the action of wind waves in the reservoir of the Ilha Solteira dam, considering measured wind velocities and a complex bathymetry. The studied area is close to a segment of the Tietê-Paraná waterway, in Brazil. Wind conditions were obtained by a 2D sonic anemometer installed in the reservoir during one of the measurement campaigns, for a period of 3 months. The estimates of the amplitude of waves generated in the reservoir were compared with measurements of the free surface elevation obtained by a Druck pressure sensor installed in the reservoir of the dam, about 300 m from the margin (already in intermediate/deep waters), and 1.0 m deep. The results obtained (amplitudes and wave periods) were shown to be promising and, albeit with significative heights overestimated, could be used for engineering preliminary drafts.
Modelo de acoplamento meteorológico-hidrodinâmico para navegação interior segura em trechos de hidrovias em reservatórios de barragens, usando um banco de dados escasso
Keywords: Dam reservoirs; Field data; SWAN model; Waterway; Wind waves